2020
DOI: 10.21203/rs.3.rs-23196/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning: a predication model of outcome of SARS-CoV-2 pneumonia

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in thousands of deaths in the world. Information about prediction model of prognosis of SARS-CoV-2 infection is scarce. We used machine learning for processing laboratory findings of 110 patients with SARS-CoV-2 pneumonia (including 51 non-survivors and 59 discharged patients). The maximum relevance minimum redundancy (mRMR) algorithm and the least absolute shrinkage and selection operator (LASSO) logistic regression model were used … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This model provided 70.25% sensitivity, 85.98% specificity and 86.78% AUC. For covid-19 detection a LASSO Logistic Regression Model was developed by [42] by using blood test results. The dataset was divided into a ratio of 80:20 and contained 110 samples.…”
Section: Related Workmentioning
confidence: 99%
“…This model provided 70.25% sensitivity, 85.98% specificity and 86.78% AUC. For covid-19 detection a LASSO Logistic Regression Model was developed by [42] by using blood test results. The dataset was divided into a ratio of 80:20 and contained 110 samples.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies have shown the impact of a critical branch of AI methods, especially the integration of ML algorithms for effective prediction models [ 31 ]. However, ML algorithms can learn and discriminate between numerous patterns in the parameters of a routine blood test.…”
Section: Introductionmentioning
confidence: 99%